Which Factors Capitalize into House Prices? A Bayesian Averaging Approach - David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2009)
This paper investigates the robustness of 31 community speci?c explanatory variables for house prices in the Swiss metropolitan area of Zurich using Bayesian Model Averaging. The main variables which capitalize with a high posterior prob- ability are location speci?c real estate characteristics, municipal taxes and ex- penditures for culture, health and social services. Demographic as well as other socioeconomic controls seem to be of minor importance. The analysis suggests a minimal list of variables that may be included in any estimation for capitalization of community speci?c characteristics in the context of a metropolitan area in a highly developed country.
Keywords: R21; C11; H40; 330; Capitalization; House Price Hedonic; Taxes; Model Uncertainity; Bayesian Model Averaging